Find expert answers and community insights on IDNLearn.com. Find the information you need quickly and easily with our reliable and thorough Q&A platform.
Sagot :
Let's break down the steps needed to find the inverse function \( f^{-1}(x) \) for the given function \( f(x) = \sqrt{7x - 21} \). Here are the steps in the correct order:
1. Start with the given function and replace \( f(x) \) with \( y \):
[tex]\[ y = \sqrt{7x - 21} \][/tex]
2. Square both sides to eliminate the square root:
[tex]\[ y^2 = 7x - 21 \][/tex]
3. Solve for \( x \):
[tex]\[ y^2 + 21 = 7x \][/tex]
4. Isolate \( x \):
[tex]\[ x = \frac{1}{7} y^2 + 3 \][/tex]
Since we are solving for \( f^{-1}(x) \), we swap \( x \) and \( y \):
5. Replace \( y \) with \( x \) as a last step:
[tex]\[ y = \frac{1}{7} x^2 + 3 \][/tex]
Thus, the steps to find the inverse function \( f^{-1}(x) = \frac{1}{7} x^2 + 3 \) are as follows:
[tex]\[ \begin{array}{c} x=\sqrt{7 y-21} \\ x^2+21=7 y \\ \frac{1}{7} x^2+3=y \\ \frac{1}{7} x^2+3=f^{-1}(x), \text { where } x \geq 0 \end{array} \][/tex]
Hence, the correct order of steps is:
1. \( x = \sqrt{7y - 21} \)
2. \( x^2 + 21 = 7y \)
3. \( \frac{1}{7} x^2 + 3 = y \)
4. \( \frac{1}{7} x^2 + 3 = f^{-1}(x), \text{ where } x \geq 0 \)
These steps properly illustrate the process of finding the inverse function.
1. Start with the given function and replace \( f(x) \) with \( y \):
[tex]\[ y = \sqrt{7x - 21} \][/tex]
2. Square both sides to eliminate the square root:
[tex]\[ y^2 = 7x - 21 \][/tex]
3. Solve for \( x \):
[tex]\[ y^2 + 21 = 7x \][/tex]
4. Isolate \( x \):
[tex]\[ x = \frac{1}{7} y^2 + 3 \][/tex]
Since we are solving for \( f^{-1}(x) \), we swap \( x \) and \( y \):
5. Replace \( y \) with \( x \) as a last step:
[tex]\[ y = \frac{1}{7} x^2 + 3 \][/tex]
Thus, the steps to find the inverse function \( f^{-1}(x) = \frac{1}{7} x^2 + 3 \) are as follows:
[tex]\[ \begin{array}{c} x=\sqrt{7 y-21} \\ x^2+21=7 y \\ \frac{1}{7} x^2+3=y \\ \frac{1}{7} x^2+3=f^{-1}(x), \text { where } x \geq 0 \end{array} \][/tex]
Hence, the correct order of steps is:
1. \( x = \sqrt{7y - 21} \)
2. \( x^2 + 21 = 7y \)
3. \( \frac{1}{7} x^2 + 3 = y \)
4. \( \frac{1}{7} x^2 + 3 = f^{-1}(x), \text{ where } x \geq 0 \)
These steps properly illustrate the process of finding the inverse function.
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.